2000
DOI: 10.1083/jcb.151.7.1501
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Programs of Gene Expression Control Morphogenetic Protein Localization

Abstract: Genomic studies in yeast have revealed that one eighth of genes are cell cycle regulated in their expression. Almost without exception, the significance of cell cycle periodic gene expression has not been tested. Given that many such genes are critical to cellular morphogenesis, we wanted to examine the importance of periodic gene expression to this process. The expression profiles of two genes required for the axial pattern of cell division, BUD3 and BUD10/AXL2/SRO4, are strongly cell cycle regulated. BUD3 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Because plasma membrane and cell wall proteins travel to the cell surface in secretory vesicles, and because the traffic of such vesicles to the cell surface is normally rapid (Novick et al, 1981;Pastor et al, 1982;Novick and Schekman, 1983), it seems that in the absence of additional mechanisms, the synthesis of such a protein at a specific time in the cell cycle would automatically determine its incorporation into the membrane or wall in a specific pattern. Thus, the normal pulse of AXL2 expression in late G 1 seems to allow the incorporation of Axl2p specifically at the presumptive bud site (at which it remains as the bud emerges); artificial expression of AXL2 in S/G2 led to the incorporation of Axl2p throughout the bud membrane (Lord et al, 2000). Similarly, the induction of ␣-agglutinin expression by Mata pheromone , coinciding with the polarization of the actin cytoskeleton toward the pheromone source (Hašek et al, 1987), seems to be sufficient to explain its localized incorporation into the shmoo tip ).…”
Section: Mechanisms For Localized Incorporation Of Cell Surface Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because plasma membrane and cell wall proteins travel to the cell surface in secretory vesicles, and because the traffic of such vesicles to the cell surface is normally rapid (Novick et al, 1981;Pastor et al, 1982;Novick and Schekman, 1983), it seems that in the absence of additional mechanisms, the synthesis of such a protein at a specific time in the cell cycle would automatically determine its incorporation into the membrane or wall in a specific pattern. Thus, the normal pulse of AXL2 expression in late G 1 seems to allow the incorporation of Axl2p specifically at the presumptive bud site (at which it remains as the bud emerges); artificial expression of AXL2 in S/G2 led to the incorporation of Axl2p throughout the bud membrane (Lord et al, 2000). Similarly, the induction of ␣-agglutinin expression by Mata pheromone , coinciding with the polarization of the actin cytoskeleton toward the pheromone source (Hašek et al, 1987), seems to be sufficient to explain its localized incorporation into the shmoo tip ).…”
Section: Mechanisms For Localized Incorporation Of Cell Surface Proteinsmentioning
confidence: 99%
“…We also found that haploid and diploid cwp1⌬ cells did not differ significantly from wild type in growth rate, overall cell morphology, or appearance after staining chitin with CFW (our unpublished data). The localization of Cwp1p to the birth scar suggested that it might have a role in cell division and/or in bud site selection (which involves cortical marker proteins that are localized to the cell poles; Lord et al, 2000;Harkins et al, 2001;Kang et al, 2004). However, because the percentage of budded cells with septa visible by DIC microscopy did not differ between cwp1⌬ and wild-type strains (31 and 32% for exponentially growing populations of strains LSY265 and YEF473, respectively), there seemed to be no delay in cell separation.…”
Section: Possible Functions Of Cwp1pmentioning
confidence: 99%
See 1 more Smart Citation
“…In haploid cells, bud site selection, which leads to formation of the daughter cell, correlates with assembly of a cortical patch of proteins with specialized functions (see below) adjacent to the preceding bud site. Assembly of this patch is temporally controlled by cell-cycle-dependent expression of genes such as AXL2 [21], and is thought to be spatially defined by septins, novel components of the membrane skeleton that form a ring structure before cytokinesis [22 • ] (Figure 1c). The cortical patch comprises Bud3p, Bud4p, Axl1p and the transmembrane protein Axl2p (reviewed in [22 • ]).…”
Section: Molecular Cues and Membrane Domains Regulating Spatial Contrmentioning
confidence: 99%
“…Beginning at the G 1 3 S transition of the cell cycle, the secretory pathway focuses on the bud site and expands the bud that shall become a daughter cell (13). Lte1p localization (which is regulated via phosphorylation, Ref.…”
mentioning
confidence: 99%